2020
DOI: 10.3748/wjg.v26.i25.3686
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with gastroenteropancreatic tumours: A systematic literature review

Abstract: BACKGROUND Gastroenteropancreatic neuroendocrine tumours (GEP-NETs) are slow-growing cancers that arise from diffuse endocrine cells in the gastrointestinal tract (GI-NETs) or the pancreas (P-NETs). They are relatively uncommon, accounting for 2% of all gastrointestinal malignancies. The usual treatment options in advanced GEP-NET patients with metastatic disease include chemotherapy, biological therapies, and peptide receptor radionuclide therapy. Understanding the impact of treatment on GEP-NET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…The findings of the present study confirm these benefits for the QLQ-GINET21. While some clinicians may be reluctant to systematically administer PROMs due to concerns about the associated increase in workload and/or misconceptions about the utility of such instruments [22], assessing patient perspectives has become increasingly relevant, particularly in patients with GI-NETs, who have a relatively long life expectancy and for whom quality of life is a key outcome measure [23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of the present study confirm these benefits for the QLQ-GINET21. While some clinicians may be reluctant to systematically administer PROMs due to concerns about the associated increase in workload and/or misconceptions about the utility of such instruments [22], assessing patient perspectives has become increasingly relevant, particularly in patients with GI-NETs, who have a relatively long life expectancy and for whom quality of life is a key outcome measure [23].…”
Section: Discussionmentioning
confidence: 99%
“…1) versus the other dimensions is not surprising given that this dimension comprises the most complex aspects of patient care, and patient-reported data are only one piece of the complex clinical picture that the clinician must consider. Moreover, the capacity of this instrument to help improve clinical decision-making is limited by the fact that the minimal clinical important differences (MCID) for this instrument have yet to be defined [23].…”
Section: Therapeutic and Clinical Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, PRRT has been reliably shown to improve scores in the QLQ‐C30 domains global QoL, diarrhoea, insomnia and appetite loss, 12 as well as time to deterioration in other domains 13 . A recently published review noted that no studies had investigated how disease stage and tumour function affected HRQoL in GEP‐NET patients 14 . However, one study, not included in the above‐mentioned review, did indeed examine the relationship between tumour burden and HRQoL, and reported a moderate correlation between a nonstandard version of tumour stage and total scores of Norfolk QoL‐NET and the GI.NET21 module 15 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the evidence needs to be comprehensive, that is, include all or nearly all important outcomes, as patients may favour HRQoL prospects over prolonged survival (Shrestha et al, 2019). Previous systematic reviews have described HRQoL and oncological outcomes of treatments separately (Jimenez-Fonseca et al, 2015;Watson et al, 2020). However, to our knowledge, no publication has reported the effects of treatments on survival, tumour regression, adverse events and HRQoL together.…”
Section: Introductionmentioning
confidence: 99%